Review on motorization and use of public transport in Perak Malaysia: realities and challenges - Suwardo, Suwardo; Napiah, Madzlan; Kamaruddin, Ibrahim (2008)

(untitled)
This paper presents about the reality of motorization phenomena and the use of public transport in Perak, Malaysia. The quantitative analysis to be performed to show the existing motorization trend against some other factors related. Data set collected, such as population, socio-economic, vehicle registration, accident data, and other factors were used for analyzing the characteristics and indicators of motorization. Statistical test was carried out for validation of model parameters. The impacts of motorization and some transportation problems were extensively discussed. Congestion, road accidents, noise, pollution, fuel consumption are among the important issues related with motorization problems. Promoting of public transport currently becomes interesting choice in anticipating the serious trend of motorization. Otherwise, the near future challenges of motorization are transport management to minimize congestion, accidents, noise, pollution and fuel consumption and promoting the use of public transport. The results indicate the remarks on impacts of motorization and some potential anticipation. The public awareness in advantages of public transport use will encourage the success of promoting public transport and will empower the people to use public transport as an alternative to reduce private cars use.